2005
DOI: 10.1016/j.jtcvs.2005.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous management of congenital tracheal stenosis and cardiac anomalies in infants

Abstract: We advocate our current strategy for infants with congenital tracheal stenosis: resection with end-to-end anastomosis and simultaneous repair of associated intracardiac anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 11 publications
4
34
0
Order By: Relevance
“…Only a few case reports have focused on LPAS with TOF, DORV, or PAPVC3161718. Consistent with previous reports, our study showed one case each with PAPVC and TOF.…”
Section: Discussionsupporting
confidence: 92%
“…Only a few case reports have focused on LPAS with TOF, DORV, or PAPVC3161718. Consistent with previous reports, our study showed one case each with PAPVC and TOF.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies reported that slide tracheoplasty was a preferred method for long-segmental stenosis [10,11]. And several studies demonstrated that simultaneous repair of CTS and cardiac anomalies is a reasonable surgical approach [12,13]. But staged correction may be considered in infants with long-segment CTS and complex cardiac anomalies because those still remain difficult to treat [5].…”
Section: Discussionmentioning
confidence: 99%
“…If an airway obstruction in infants with CHD undergoing surgical intervention is not resolved simultaneously, the majority of such children will remain dependent on a breathing machine as long as 7 days [Elliott et al 2003;Loukanov et al 2005]. In this study, we carried out radical surgical intervention for CHD and attempted to withdraw patients from the breathing machine, but it was unsuccessful due to associated airway obstruction in 22 patients.…”
Section: Discussionmentioning
confidence: 99%